Iowa field report contributed by Chris Edwards, spring 1996 - Edwards, Chriset al (1996)
Spring report of birds found in eastern Iowa contributed by Chris Edwards. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1996. Epson - sheet feed